2012
DOI: 10.1007/s11655-012-1299-x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific validation of the ethnomedicinal properties of the Ayurvedic drug Triphala: A review

Abstract: Triphala, a herbal formula composed of the three fruits of Terminalia chebula Retz. (Haritaki, Family: Combretaceae), Terminalia bellirica Roxb. (Bibhitaki, Family: Combretaceae) and Phyllanthus emblica Linn. or Emblica officinalis Gaertn. (Amalaki or the Indian gooseberry, Family: Euphorbiaceae) is considered to be a universal panacea in the traditional Indian system of medicine the Ayurveda. It has been described in the Ayurveda text as a "Rasayana' and to rejuvenat the debilitated organs. Ayurvedic physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 30 publications
0
74
0
Order By: Relevance
“…It has been widely described as a rejuvenator in Ayurvedic medicine. Triphala has notable health benefits as an effective antioxidant, chemopreventive, radioprotective, antidiabetic, and hypolipidemic agent both in vitro and in vivo [11, 12]. It has also been clinically proven to be a promising antiplaque and antigingivitis agent [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely described as a rejuvenator in Ayurvedic medicine. Triphala has notable health benefits as an effective antioxidant, chemopreventive, radioprotective, antidiabetic, and hypolipidemic agent both in vitro and in vivo [11, 12]. It has also been clinically proven to be a promising antiplaque and antigingivitis agent [13].…”
Section: Introductionmentioning
confidence: 99%
“…Triphala is a well‐known ancient Ayurvedic Indian powdered preparation, and has been traditionally used as a laxative in chronic constipation, indigestion, hypertension, serum cholesterol reduction, poor liver function, and ulcerative colitis . Scientific studies carried out in the past two decades have validated many ethnomedicinal claims, and have showed triphala to possess free‐radical‐scavenging, antioxidant, anti‐inflammatory, antipyretic, analgesic, antibacterial, antimutagenic, wound‐healing, anticariogenic, antistress, adaptogenic, hypoglycemic, anticancer, chemoprotective, radioprotective, and chemopreventive effects …”
Section: Introductionmentioning
confidence: 99%
“…14 Scientific studies carried out in the past two decades have validated many ethnomedicinal claims, and have showed triphala to possess free-radical-scavenging, antioxidant, anti-inflammatory, antipyretic, analgesic, antibacterial, antimutagenic, wound-healing, anticariogenic, antistress, adaptogenic, hypoglycemic, anticancer, chemoprotective, radioprotective, and chemopreventive effects. 15 Triphala alcohol extracts, which are used as mouth rinse, have been shown to be effective against plaque, gingivitis, and dental caries in a large-scale, 1-year follow-up study conducted among Indian children. 13 Maurya et al 16 reported on the relief experienced by patients with various periodontal symptoms after using triphala mouth rinse.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have validated many of the properties claimed by historical evidence and the more recent ethno medical studies [17].…”
Section: Introductionmentioning
confidence: 57%